Optical non-linearities and applications of ZnS phosphors - Chauhan, Ayushi; Sharma, Rajesh; Singh, Manjot; Sharma, Reena (Advanced Optical Technologies, 2024)
Optical nonlinearities play a crucial role in enabling efficient and ultrafast switching applications that are essential for next-generation photonic devices. ZnS phosphor material produces the best results in terms of increased luminescence quantum yield when doped with certain impurities. Nevertheless, the investigation of the third-order nonlinear optical susceptibility of the phosphor materials can be exploited for various switching applications. In this regard, we review the recent advancements in the investigation of nonlinear optical properties of ZnS phosphors, where the knowledge of absorption and refraction is utilized in various optical and detector applications. Furthermore, the review highlights strategies employed to enhance the nonlinear optical response of phosphor materials as well as a general discussion of an attosecond optical switching scheme which can be used to fabricate devices with petahertz speeds. Consequently, we provide a solution to the unsolved problem of the significant extension of optical limiting applications to switching applications by developing design strategies to manipulate conventional ZnS phosphor material. The potential challenges and future prospects of utilizing phosphor materials for switching applications are also addressed. The strategies for manipulating ZnS phosphor can be generalized for a broad range of other materials by minimizing linear and nonlinear losses, while enhancing the values of the nonlinear refractive index coefficient. We propose that the figure-of-merit of ZnS material can be enhanced by using a suitable combination of pump and probe wavelength values, which can be useful for optical switching applications.